Բնակավայրերի տեղաբաշխման և բնակչության շարժընթացի աշխարհագրական հիմնահարցերը Մեղրիի տարածաշրջանում - Ալեքսանյան, Կ. Բ. (Մանկավարժ հրատ․)
Հոդվածը նվիրված է Հայաստանի Սյունիքի մարզի Մեղրիի տարածաշրջանի բնակավայրերի տեղաբաշխման և բնակչության շարժընթացի առանձնահատկությունների լուսաբանմանն ու դրանց միտումների դիտարկմանը: Հոդվածում պարզաբանվում են Մեղրիի տարածաշրջանի բնակավայրերի տեղաբաշխման, լքված բնակավայրերի առաջացման պատճառների, բնակչության շարժի փոփոխությունների առանձնահատկությունները: В исследовании были обсуждены и проанализированы характиристики распределения населения и населенных пунктов в Мегринском регионе. Были изучены действующие и заброшенные села, которые образовались в силу исторических, сициальных и политических событий. А также ь этом регионе анализированы данные о динамике населения с 1968-2020гг. Общее число населения Мегринского района с 1968г до сих пор уменьшилось почти 3000 человек. По нашему мнению 15 населенных пунктов Мегринского района можно группировать следующим образом: ՜а/ Поселения Приараксинского и предгорного пояса : Агарак, Карчеван, Мегри, Алванк, Легваз,Шванидзор, Нрнадзор (600-1000м над уровнем моря). б/ Поселения среднегорного пояса (1000-1700м): Варданидзор, Вагравар, Гудемнис, Курис, Тхкут, Айгедзор. в/ Поселения высоскогорного пояса (1700-2000м): Личк и Таштун. In the study have been discussed and analyzed the characteristics of the distribution of population and settlements in the Meghri region. Have been discussed abandoned villages that were formed due to historical, social and political events. And also in this region were analyzed population dynamics of 1968-2020 data. In our opinion, the 15 settlements in the region can be grouped as follows: a) Lowland settlements` Agarak, Karchevan, Meghri, Alvanq, Lehvaz, Shvanidzor, Nrnadzor (600-1000m height). b) Middle zone settlements – the highest are from 1000 meters to 1700 m, where are Vardanidzor, Vahravar, Gudemnis, Kuris, Tkhkut and Aygedzor settlements. c) The settlements of mountain zone (1700m – 2000m) Lichq and Tashtun. It should be noted, that according to 13 out of 127 rural settlements and 2 out of 7 urban settlements of Syunik region are scattered in accordance with the slope of the surface in Meghri region, which cover the valley zone of near areas of Araks and gradually decreases from south to north.
Keywords: Աշխարհագրություն